Locke, Arnauld, and Abstract Ideas - Pearce, Kenneth (My University, 2019)
A great deal of the criticism directed at Locke’s theory of abstract ideas assumes that a Lockean abstract idea is a special kind of idea which by its very nature either represents many diverse particulars or represents separately things that cannot exist in separation. This interpretation of Locke has been challenged by scholars such as Kenneth Winkler and Michael Ayers who regard it as uncharitable in light of the obvious problems faced by this theory of abstraction. Winkler and Ayers argue that Locke instead held that to have an abstract idea is to attend selectively to some portion of the content of a particular idea. On this view, to have an abstract idea is not to have a special kind of idea but to have an ordinary idea in a special way. Ayers argues that Locke inherited this theory from Arnauld. I argue that the case made by Ayers for the attribution of the extrinsic theory to Locke rests on a misinterpretation of Arnauld. In fact, both Locke and Arnauld regard selective attention as part of a process whereby a new kind of idea is constructed.
PUBLISHED
Keywords: John Locke; Antoine Arnauld; Abstract ideas; Mental imagery; Mental representation; Antoine Arnauld; John Locke; Philosophy of mind